Rapid Emergence of Daptomycin Resistance in Clinical Isolates of Corynebacterium striatum… A Cautionary Tale - TeKippe, Erin McElvania (Eur J Clin Microbiol Infect Dis, 2014)
PURPOSE: The objective of this study was to investigate the observation of daptomycin resistance in Corynebacterium striatum, both in vivo and in vitro. We describe a case of C. striatum bacteremia in a patient with a left ventricular assist device (LVAD); the initial isolate recovered was daptomycin susceptible with a minimum inhibitory concentration (MIC) of 0.125 μg/ml. Two months later, and after daptomycin therapy, the individual became bacteremic with an isolate of C. striatum with a daptomycin MIC of >256 μg/ml. METHODS: To study the prevalence of daptomycin resistance in C. striatum, clinical isolates of C. striatum were grown in broth culture containing daptomycin to investigate emergence of resistance to this antimicrobial. Molecular typing was used to evaluate serial isolates from the index patient and the clinical isolates of C. striatum we assayed. RESULTS: In vitro analysis of isolates from the index patient and seven of eleven additional C. striatum isolates exhibited emergence of high level daptomycin resistance, despite initially demonstrating low MICs to this antimicrobial agent. This phenotype was persistent even after serial subculture in the absence of daptomycin. CONCLUSIONS: Together, these data demonstrate that caution should be taken when using daptomycin to treat high-inoculum infections and/or infections of indwelling medical devices with C. striatum. To our knowledge, this is the first report characterizing emergence of daptomycin resistance in C. striatum.